Security Camera Real Time Recorder for Personal Property's Room Surveillance - Abdelrahman, Waled Abubakr (2010)
One of the sections most interesting in the existing systems on the computer is Computer vision. There are many applications commercial for video surveillance for internal and external monitoring of both, and tracking systems for the security by use multiple cameras or one. And tracking of security should be capable to face effectively handle two main areas, a first stage for the detection of object movement and the second stage is track the object through numerous fiames. The objective of this project is to develop not expensive tracking system security in the places indoor as room, and it will be able to determine automatically, and classification and tracking of an object by using one web cam. The research methodology for develop and evaluate the prototype was adapted from the waterfall module and it contains five stages: requirements, design, implementation, verification and maintenance. Usefulness, Ease of Use and Outcome and Future Use were used to indicate for good usability from Results of user evaluation on the SCRTRS.